2021
DOI: 10.3390/nano11020387
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Icariin/β-CD-IC/Bacterial Cellulose with Enhanced Biomedical Potential

Abstract: A “super” bioactive antibacterial hydrogel, Icariin-β-CD-inclusion complex/Bacterial cellulose and an equally capable counterpart Icariin-Bacterial cellulose (ICBC) were successfully produced with excellent antioxidant properties. The highly porous hydrogels demonstrated very high fluid/liquid absorption capability and were functionally active as Fourier Transform Infrared Spectrometer (FTIR) test confirmed the existence of abundant hydroxyls (-OH stretching), carboxylic acids (-CH2/C-O stretching), Alkyne/nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…As a flavone compound, ICA is likely to have antioxidant activity through the scavenging of free radicals, or by chelating metal ions or by inhibiting the enzymatic systems responsible for producing free radicals (62). In a recent study, ICA was demonstrated to have radical scavenging activities using a 2,2'-diphenyl-1-picrylhydrazyl radical scavenging assay (63). It is hypothesized that the phenol functional groups in ICA could undergo H-atom abstraction for stable and delocalized radical species (63).…”
Section: Discussionmentioning
confidence: 99%
“…As a flavone compound, ICA is likely to have antioxidant activity through the scavenging of free radicals, or by chelating metal ions or by inhibiting the enzymatic systems responsible for producing free radicals (62). In a recent study, ICA was demonstrated to have radical scavenging activities using a 2,2'-diphenyl-1-picrylhydrazyl radical scavenging assay (63). It is hypothesized that the phenol functional groups in ICA could undergo H-atom abstraction for stable and delocalized radical species (63).…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose‐based wound dressings have been developed as an alternative to traditional wound dressings. Cellulose‐based dressings can provide an absorbent, non‐adhesive, and non‐irritating surface for wound healing, while also allowing for moisture regulation and gas exchange 66,67 …”
Section: Cellulosementioning
confidence: 99%
“…Cellulose-based dressings can provide an absorbent, non-adhesive, and non-irritating surface for wound healing, while also allowing for moisture regulation and gas exchange. 66,67…”
Section: Wound Dressingsmentioning
confidence: 99%
“…In a study by Mensah et al, the icariin/β–CD inclusion complex/bacterial cellulose (ICPBC) product was created in the form of hydrogels, which can be used in different fields, acting as target drug carriers, for wound dressings, or as facemasks in the cosmetics industry. In vitro studies showed the increased drug release (up to 47.9%) of icariin in the case of ICPBC [ 72 ].…”
Section: Bioavailability Improvementsmentioning
confidence: 99%